ABA‐triggered ROS burst in rice developing anthers is critical for tapetal programmed cell death induction and heat stress‐induced pollen abortion. (7th February 2023) - Zhao, Qian; Guan, Xianyue; Zhou, Lujian; Asad, Muhammad‐Asad‐Ullah; Xu, Yanqiu; Pan, Gang; Cheng, Fangmin
Abstract: High temperatures (HT) cause pollen abortion and poor floret fertility in rice, which is closely associated with excessive accumulation of reactive oxygen species (ROS) in the developing anthers. However, the relationships between accumulation of abscisic acid (ABA) and ROS, and their effects on tapetum‐specific programmed cell death (PCD) in HT‐stressed anthers are poorly characterised. Here, we determined the spatiotemporal changes in ABA and ROS levels, and their relationships with tapetal PCD under HT exposure. Mutants lacking ABA‐activated protein kinase 2 (SAPK2) functions and exogenous ABA treatments were used to explore the effects of ABA signalling on the induction of PCD and ROS accumulation during pollen development. HT‐induced pollen abortion was tightly associated with ABA accumulation and oxidative stress. The higher ABA level in HT‐stressed anthers resulted in the earlier initiation of PCD induction and subsequently abnormal tapetum degeneration by activating ROS accumulation in developing anthers. Interactions between SAPK2 and DEAD‐box ATP‐dependent RNA helicase elF4A‐1 (RH4) were required for ABA‐induced ROS generation in developing anthers. The OsSAPK2 knockout mutants showed the impaired PCD responses in the absence of HT. However, the deficiency of SAPK2 functions did not suppress the ABA‐mediated ROS generation in HT‐stressed anthers. Summary statement: High temperatures (HT) disturbed the cellular distributions of ABA and ROS contents in rice anthers. The higher ABA in HT‐stressed anthers contributed to HT‐induced pollen abortion by activating ROS generation and oxidation in developing anthers. Interactions between SAPK2 and DEAD‐box ATP‐dependent RNA helicase elF4A‐1 (RH4) were required for ABA‐induced ROS generation during pollen development and its response to HT exposure.